Beta-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material as well as preparation method and application thereof
Through the composite of β-naphthol-based trifunctional resin and diethylene triamine and carbon fiber, the brittleness and hygroscopicity of epoxy resin are solved, and the mechanical properties and heat resistance of the composite material are improved. It is suitable for many high-performance applications field.
Patent Information
- Application Number
- CN202411665202.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-14
AI Technical Summary
The existing multifunctional epoxy resin has problems with brittleness and hygroscopicity, resulting in poor physical and mechanical properties and short service life.
Use β-naphthol-based trifunctional resin and diethylene triamine to mix and coat on carbon fibers. After high temperature curing and pressing, a β-naphthol-based trifunctional resin/carbon fiber/diethylene triamine composite material is formed to improve the resin Reactive activity and crosslinking density enhance the mechanical properties and chemical stability of composite materials.
It realizes high strength, high modulus, good heat resistance and chemical stability of composite materials, extends service life, and is suitable for aerospace, automobiles and electronics fields.
Smart Images

Figure CN119306984A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer resins, and in particular relates to a β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material and a preparation method and application thereof. Background Art
[0002] As the demand for electricity continues to increase, the development of long-distance, large-capacity high-voltage direct current (HVDC) systems is becoming increasingly popular. Coupled with the trend of miniaturization and integration of electronic and electrical equipment, these advances have increased the requirements for many physical properties of insulation materials. Insulation materials need to provide not only excellent electrical insulation properties, but also excellent thermal stability and mechanical properties.
[0003] Epoxy resins are gaining more and more popularity in the field of fiber reinforced composites due to their good heat resistance, good bonding properties, and good mechanical properties. The performance of cured epoxy resins is highly related to their network structure, which is heavily affected by the functionality of the epoxy resin. Improving the functionality of epoxy resins is one of the effective ways to achieve high strength and high modulus epoxy resin systems. Multifunctional epoxy resins are a method to improve heat resistance due to their high cure density. Multifunctional epoxy resins are known for their improved mechanical, chemical, thermodynamic, and electrical properties. Other advantages of multifunctional epoxy resins are high glass transition temperature, high decomposition temperature, good long-term high temperature performance, and good wet strength. However, multifunctional epoxy resins also have some inherent limitations, such as greater brittleness and easy absorption of moisture from the environment. These problems become more obvious with the increase of network crosslinking density, which has an adverse effect on the physical and mechanical properties of the material. In order to overcome these shortcomings, researchers have conducted in-depth research on epoxy resins with different functional groups. For example, the dynamic, mechanical and fracture properties of three epoxy resins with different functional groups were studied, and it was found that the glass transition temperature (Tg) changes with the change of functional groups, while the strain energy release rate and stress intensity factor do not change significantly with the functional groups. In addition, in order to further improve the mechanical properties and corrosion resistance of epoxy resins, researchers have tried to dope carbon fibers during the synthesis process to form epoxy-based fiber composites. This composite material has broad application prospects in many fields such as automobiles, power transmission, construction, and aerospace, mainly due to its excellent mechanical properties, dimensional stability and corrosion resistance.
[0004] In view of the inherent brittleness and hygroscopicity problems of existing multifunctional epoxy resins, which seriously affect the physical and mechanical properties and service life of the materials, it is necessary to develop an epoxy resin formula with strong electrical properties that will not cause a decrease in mechanical strength after curing, and the main agent and curing agent can be matched with each other to achieve the best overall performance. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material and its preparation method and application, so as to solve the inherent brittleness and hygroscopicity problems of existing multifunctional epoxy resins, resulting in poor physical and mechanical properties of the material and a short service life.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention discloses a preparation method of a β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material, comprising: uniformly mixing the β-naphthol trifunctional resin and diethylenetriamine and coating the mixture on a plurality of carbon fibers, and performing high temperature curing, pressing, and cooling to obtain the β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material;
[0008] The β-naphthol-based trifunctional resin is prepared by polymerization of β-naphthol, formaldehyde and epichlorohydrin under alkaline medium conditions.
[0009] Preferably, the molar ratio of β-naphthol-based trifunctional resin: diethylenetriamine: carbon fiber is (70-85): (1-10): (10-30).
[0010] Preferably, the high temperature curing temperature is 70-100° C.; the high temperature curing time is 1.5-2.5 h; the pressing pressure is 45-60 psi; the pressing temperature is 80-85° C.; and the pressing time is 2-5 min.
[0011] Preferably, the preparation method of the β-naphthol-based trifunctional resin comprises: adding β-naphthol and formaldehyde into a beaker, heating and stirring evenly, adding epichlorohydrin and NaOH aqueous solution, heating and stirring evenly, adding methyl ethyl ketone, desalting, and distilling the resin to obtain the β-naphthol-based trifunctional resin.
[0012] Further preferably, the dosage ratio of β-naphthol: formaldehyde: epichlorohydrin: NaOH aqueous solution: methyl ethyl ketone is (0.8-1.2) mol: (1.5-2.5) mol: (2-4) mol: (2-2.5) mol: (50-100) mL; the mass fraction of NaOH aqueous solution is 40%.
[0013] More preferably, the temperature of heating and stirring is 45-65° C., and the time is 1.5-2.5 h.
[0014] More preferably, the temperature of the heating and stirring is 70-90° C., and the time is 3-4 h.
[0015] More preferably, the temperature of the distilled resin is 118° C., the time of the distilled resin is 3-4 hours, and the reaction yield of the β-naphthol-based trifunctional resin is 80%-87%.
[0016] The invention also discloses a β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material prepared by the preparation method, which has a tensile strength of 80.0-82.4 MPa, a flexural strength of 190.5-199.2 MPa, an impact strength of 7.80-8.00 J / cm, and a glass transition temperature of 180-183°C.
[0017] The invention also discloses the application of the beta-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material prepared by the preparation method in the preparation of insulating materials.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The invention discloses a preparation method of a β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material; the method comprises: uniformly mixing the β-naphthol trifunctional resin and diethylenetriamine and coating the mixture on a plurality of carbon fibers; by mixing the β-naphthol trifunctional resin and diethylenetriamine, the reaction activity and crosslinking density of the resin can be increased, thereby improving the mechanical properties and chemical stability of the composite material. Coating the mixture on the carbon fibers can make full use of the high strength and high modulus characteristics of the carbon fibers and enhance the overall performance of the composite material; after high temperature curing, pressing and cooling, a β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material is obtained; high temperature curing can promote the crosslinking reaction of the functional groups in the resin to form a stable network structure, thereby improving the heat resistance and dimensional stability of the composite material. At the same time, the curing process can also eliminate the residual stress and bubbles in the material, improve the microstructure and performance of the material; the pressing process can make the fibers and resin in the composite material more closely combined, reduce pores and defects, and improve the density and mechanical properties of the composite material. In addition, pressing can also enable the composite material to obtain the desired shape and size. The cooling process can fix the shape and size of the composite material, while reducing the residual stress and deformation of the material. The resulting composite material has excellent mechanical properties, chemical stability and heat resistance, and can be widely used in aerospace, automotive, electronics and other fields. β-naphthol-based trifunctional resin is prepared by polymerization of β-naphthol, formaldehyde and epichlorohydrin under alkaline medium conditions; this synthesis method can introduce multiple functional groups, making the resin have higher reactivity and cross-linking ability. At the same time, β-naphthol as a raw material gives the resin excellent heat resistance and chemical stability. This resin, as the matrix of the composite material, can significantly improve the overall performance of the composite material.
[0020] Furthermore, the molar ratio of β-naphthol trifunctional resin: diethylenetriamine: carbon fiber is (70-85): (1-10): (10-30); by precisely controlling the dosage ratio of each component, the performance of the composite material can be optimized. A higher resin content can improve the strength and toughness of the composite material, while an appropriate amount of carbon fiber can enhance the rigidity and wear resistance of the composite material. At the same time, an appropriate amount of diethylenetriamine as a curing agent can ensure sufficient curing of the resin and improve the stability and durability of the composite material.
[0021] Furthermore, the temperature of high temperature curing is 70-100°C; the time of high temperature curing is 1.5-2.5h; the pressing pressure is 45-60psi; the pressing temperature is 80-85°C; the pressing time is 2-5min; by adjusting the temperature and time of high temperature curing, the curing degree of the resin and the performance of the composite material can be controlled. Appropriate curing temperature and time can ensure sufficient cross-linking of the resin and improve the heat resistance and mechanical properties of the composite material. By setting appropriate pressing parameters, it can be ensured that the resin and carbon fiber in the composite material are closely combined, pores and defects are reduced, and the density and mechanical properties of the composite material are improved.
[0022] Furthermore, a method for preparing a β-naphthol-based trifunctional resin comprises: adding β-naphthol and formaldehyde into a beaker, heating and stirring evenly, adding epichlorohydrin and an aqueous NaOH solution, heating and stirring evenly, adding methyl ethyl ketone, desalting, distilling the resin, and controlling the temperature to remove methyl ethyl ketone at 79.6° C., remove water at 100° C., and remove epichlorohydrin impurities at 117.9° C. to obtain a β-naphthol-based trifunctional resin; the resin has multiple functional groups and can react with carbon fiber and diethylenetriamine to form a stable cross-linked structure, thereby improving the performance of the composite material.
[0023] Furthermore, the dosage ratio of β-naphthol: formaldehyde: epichlorohydrin: NaOH aqueous solution: methyl ethyl ketone is (0.8-1.2) mol: (1.5-2.5) mol: (2-4) mol: (2-2.5) mol: (50-100) mL; the mass fraction of the NaOH aqueous solution is 40%; by precisely controlling the dosage ratio of the raw materials and the concentration of the NaOH aqueous solution, the smooth progress of the resin synthesis can be ensured and the performance of the resin can be optimized. This ratio can ensure that the resin has sufficient functional groups and reaction activity, providing a good basis for the subsequent preparation of composite materials.
[0024] Furthermore, the heating and stirring temperature is 45-65° C., and the time is 1.5-2.5 hours; appropriate heating and stirring temperature and time can promote the mixing and reaction of the raw materials and ensure the uniformity and stability of the resin synthesis.
[0025] Furthermore, the temperature of the heating and stirring is 70-90° C., and the time is 3-4 hours; the heating and stirring can further promote the synthesis reaction of the resin and improve the crosslinking degree and performance of the resin.
[0026] Furthermore, the temperature of the distilled resin is 118°C, the time of the distilled resin is 3-4 hours, and the reaction yield is 80%-87%. By distilling the resin, unreacted raw materials and by-products can be removed to improve the purity of the resin. The higher distillation temperature and time can ensure the full distillation and purification of the resin. At the same time, the higher reaction yield indicates that the preparation method has higher efficiency and feasibility.
[0027] The present invention also discloses a β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material prepared by the above preparation method; the tensile strength is 80.0-82.4MPa, the flexural strength is 190.5-199.2MPa, the impact strength is 7.80-8.00J / cm, and the glass transition temperature is 180-183°C; the composite material combines the high performance of the β-naphthol trifunctional resin, the reinforcing effect of the carbon fiber and the curing effect of diethylenetriamine to form a composite material with excellent performance. The composite material not only has high strength and high modulus, but also has good heat resistance and chemical stability. These specific mechanical property data prove the excellent performance of the composite material. The high tensile strength and flexural strength enable the composite material to withstand large loads and bending deformations, and is suitable for various occasions requiring high-strength materials. The high impact strength means that the composite material is not easy to break or damage when impacted, and has good impact resistance. The high glass transition temperature indicates that the composite material has excellent heat resistance and can maintain stable performance under high temperature environment.
[0028] The present invention also discloses the use of the β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material prepared by the above-mentioned preparation method in the preparation of insulating materials; when applied to the preparation of insulating materials, its excellent performance can be fully utilized. The high insulation performance and good heat resistance of the composite material make it an ideal choice for preparing high-performance insulating materials. The insulating material prepared using this composite material can not only ensure the normal operation of electrical equipment, but also improve the safety and reliability of the equipment. In addition, the composite material also has good mechanical properties, can withstand certain mechanical stress and impact, and further improves the stability and durability of the insulating material. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The schematic diagram of the preparation of the β-naphthol-based trifunctional resin of the present invention;
[0030] Figure 2 FT-IR spectra of the β-naphthol trifunctional resin and industrial epoxy resin of the present invention; DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0032] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0033] The present invention is described below with reference to specific examples. It will be appreciated by those skilled in the art that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention in any way.
[0034] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials, reagents, etc. used in the following examples are commercially available products unless otherwise specified.
[0035] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0036] See also Figure 1 The figure is a schematic diagram of the preparation principle of the β-naphthol-based trifunctional resin of the present invention; it can be seen from the figure that the theoretical molar ratio of the components involved in the reaction is β-naphthol: formaldehyde: epichlorohydrin = 1:1:1.
[0037] See also Figure 2 The FT-IR spectra of the β-naphthol trifunctional resin and the industrial epoxy resin of the present invention are shown in FIG. 1 . As can be seen from the figure, in the FT-IR spectrum, at 3415.03 cm -1 A sharp peak of -OH group was observed at 2967.12cm, but the transmittance of this peak was lower than that of industrial epoxy resin, indicating that more -OH groups were used in the reaction. -1 The sharp peak at 1611.25cm indicates CH stretching vibration.-1 The sharp peak at 1515.05 cm indicates the stretching of the aromatic ring C=C. -1 The peak at 845.12 cm indicates the stretching of the aromatic ring CC. -1 The characteristic and strong peaks of epoxy COC were observed, confirming the progress of the polymerization reaction.
[0038] The invention discloses a method for preparing a β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material. The β-naphthol trifunctional resin and diethylenetriamine are uniformly mixed and coated on a plurality of carbon fibers, and the β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material is obtained after high-temperature curing, pressing and cooling. The β-naphthol trifunctional resin is prepared by polymerization reaction of β-naphthol, formaldehyde and epichlorohydrin under alkaline medium conditions.
[0039] The molar ratio of β-naphthol trifunctional resin: diethylenetriamine: carbon fiber is (70-85): (1-10): (10-30).
[0040] The invention discloses a method for preparing a β-naphthol-based trifunctional resin, comprising the following steps:
[0041] Place a 2L three-necked flask equipped with a mechanical stirrer and a condenser in a constant temperature heating device. Under alkaline conditions, add 0.8-1.2 mol of β-naphthol and 1.5-2.5 mol of formaldehyde to the flask. Stir at a temperature of 45-65°C for 1.5-2.5 hours, then add 2-4 mol of epichlorohydrin to the reaction flask, and drip an aqueous NaOH solution (2-2.5 mol, 40% mass fraction of the solution). After the addition is completed, the temperature is raised to 70-90°C, the reaction mixture is stirred for 3-4 hours, and then 50-100 mL of methyl ethyl ketone is added as a solvent to maintain the viscosity of the resin. Desalination is carried out by vacuum distillation, and then the resin is distilled at 118°C for 3-4 hours to remove excess water, methyl ethyl ketone and epichlorohydrin, and cooled at room temperature to obtain a dark yellow, odorless β-naphthol-based trifunctional resin with a yield of 80%-87%. The reaction principle is as follows Figure 1 shown.
[0042] The invention discloses a preparation method of a β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material, comprising the following steps: preparing a fiber-reinforced composite material by using a β-naphthol trifunctional resin and carbon fiber in a ratio of 3:2. Diethylenetriamine (DETA) is used as a curing agent according to its ammonium hydroxide equivalent. The β-naphthol trifunctional resin and DETA are mixed evenly according to the required amount, and coated on 16 15cm carbon fiber cloths by a hand lay-up process. Stacked between two polytetrafluoroethylene sheets. All sheets are kept at a high temperature of 70-100°C between two plates of a molding press for 1.5-2.5h for curing, and finally pressed at 80-85°C for 2-5min under a pressure of 45-60psi to flatten it. The prepared β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material is cooled at room temperature, taken out from the two plates of the molding press, and all dimensions of the composite sheet are measured after removing the polytetrafluoroethylene sheet. The β-naphthol trifunctional resin and diethylenetriamine are cross-linked and doped with a carbon fiber structure to obtain a β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material with a high glass transition temperature and excellent heat resistance, which effectively improves the performance of epoxy resin models. The β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material (NCD) has a tensile strength of 80.0-82.4MPa, a flexural strength of 190.5-199.2MPa, an impact strength of 7.80-8.00J / cm, and a glass transition temperature of 180-183°C.
[0043] The β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material prepared by the above-mentioned preparation method disclosed in the present invention is an epoxy resin composition with excellent chemical resistance and heat resistance, comprising β-naphthol trifunctional resin, carbon fiber and curing agent diethylenetriamine; the β-naphthol trifunctional resin is generated by polymerization reaction of β-naphthol, formaldehyde and epichlorohydrin; through the cross-linking reaction of the β-naphthol trifunctional resin and the curing agent diethylenetriamine having an amino group, the epoxy resin molecular chain is made tighter, the intermolecular force is enhanced, and it is also helpful to improve the curing speed and curing degree of the epoxy resin. Diethylenetriamine is used as a curing agent, and its amino group reacts with the epoxy group in the β-naphthol trifunctional resin to form a stable cross-linked structure. Not only the curing efficiency of the epoxy resin is improved, but also the cured product has a higher hardness and glass transition temperature. The specific combination of amino curing agent and β-naphthol trifunctional resin enables the two to give full play to their respective advantages during the curing process, thereby optimizing the performance of epoxy resin, making it have high hardness, high glass transition temperature and corrosion resistance. The doping of carbon fiber significantly improves the mechanical properties of epoxy resin. The high strength and modulus of carbon fiber make the composite material have higher hardness and toughness, suitable for various high-load and impact environments.
[0044] The invention discloses an application of a β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material prepared by the above-mentioned preparation method in the preparation of an insulating material; the preparation process is relatively simple, the cost is controllable, and it is conducive to reducing production costs and improving production efficiency. Due to the tight trifunctional structure and the close combination with the carbon fiber, a stable cross-linked network is formed, thereby showing excellent electrical insulation performance. This material can effectively prevent current leakage, reduce the failure rate of electrical equipment, and ensure the safe and stable operation of the electrical system. Due to the high glass transition temperature and excellent chemical corrosion resistance, it means that it can maintain stable electrical insulation performance under high temperature and corrosive environments. This makes it particularly suitable for electrical equipment working in harsh environments such as high temperature, high humidity, and corrosive gases, such as power transformers, motors, cables, etc. Due to the high tensile strength, flexural strength and impact strength, it means that it can withstand large mechanical stress and impact, and is not prone to breakage or damage. This ensures that the insulating material can maintain stable performance during long-term use and extend the service life of electrical equipment. Compared with traditional metal insulating materials, β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite materials have lower density, so they can achieve lightweight electrical equipment. This helps to reduce the weight and volume of electrical equipment, improve the convenience of transportation and installation, and reduce energy consumption and production costs. No toxic and harmful substances are produced during the preparation process, and the material itself can be recycled, which meets environmental protection requirements. Insulating materials prepared using this material help promote the green development and sustainable development of the electrical industry. It can also promote the development and progress of related industries and promote sustainable economic development. Due to the significant improvement in the mechanical properties of the prepared β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material, its application range has been significantly broadened. In the aerospace field, it can be used to manufacture structural parts and components of aircraft such as aircraft and rockets, and withstand the challenges of high loads and extreme environments. In the field of automobile manufacturing, it can be used to manufacture components such as body and chassis to improve the safety and durability of automobiles. In the field of electronics and electrical appliances, it can be used to manufacture insulating materials, packaging materials, etc. to ensure the stable operation of electronic appliances. In addition, it can also be used in sports goods, building materials and other fields to meet the needs of different industries for high-performance composite materials.
[0045] Example 1
[0046] A method for preparing a β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material comprises the following steps:
[0047] A 2L three-necked flask equipped with a mechanical stirrer and a condenser is placed in a constant temperature heating device. In the presence of an alkaline medium, 1.0 mol of β-naphthol and 2.0 mol of formaldehyde are added to the flask. Stir at a temperature of 55°C for 1.5 hours, then add 3 mol of epichlorohydrin to the reaction flask, and drop into an aqueous solution of NaOH (2.2 mol, 40% concentration solution). After the addition is completed, the temperature is raised to 80°C, the reaction mixture is stirred for 3 hours, and then 50 mL of methyl ethyl ketone is added as a solvent to maintain the viscosity of the resin. Desalination is performed by vacuum distillation, and then the resin is distilled at 118°C for 3h to remove excess water, methyl ethyl ketone and epichlorohydrin, and cooled at room temperature to obtain a dark yellow, odorless β-naphthol trifunctional resin with a yield of 87%.
[0048] The β-naphthol trifunctional resin: diethylenetriamine: carbon fiber was reacted at a molar ratio of 75:5:25. Diethylenetriamine was used as a curing agent. The β-naphthol trifunctional resin and diethylenetriamine were mixed evenly according to the required amount and coated on 16 15cm carbon fiber cloths using a hand lay-up process. They were stacked on each other between two polytetrafluoroethylene sheets. All sheets were kept at 80°C between the two plates of the molding press for 90 minutes for high temperature curing, and finally pressed at 80°C for 2 minutes under a pressure of 50psi. The prepared β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material was cooled at room temperature, removed from the two plates of the molding press, and all dimensions of the composite sheet were measured after removing the polytetrafluoroethylene sheet. The β-naphthol trifunctional resin was cross-linked with diethylenetriamine and a carbon fiber structure was doped therein to obtain a β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material with a high glass transition temperature and excellent heat resistance, which effectively improved the performance of epoxy resin models. The tensile strength of the β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material (NCD) is 82.4MPa, the flexural strength is 199.2MPa, the impact strength is 8.00J / cm, and the glass transition temperature is 183°C. Compared with the traditional epoxy resin / carbon fiber / diethylenetriamine (ECD) with a tensile strength of 62.6MPa, a tensile strength of 141.9MPa, an impact strength of 6.89J / cm, and a glass transition temperature of 167°C, the mechanical properties are greatly improved, which broadens the application range of the resin and has important practical application value.
[0049] Performance evaluation of β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite materials:
[0050] 1. Tensile strength: Tensile strength measures the ability of a material to withstand forces that tend to pull it apart, and determines how far a material can stretch before breaking. The test was conducted on a UTM (Universal Testing Machine) Shimadzu AG 100, with a strain rate of 100% and a crosshead speed of 50 mm / min.
[0051] 2. Flexural strength: Flexural strength is the ability of a material to withstand a bending force applied perpendicular to its longitudinal axis. The stress caused by the bending load is a combination of compressive and tensile stresses. The bending properties are reported and calculated based on the maximum stress and strain occurring on the outer surface of the test bar. The test was conducted on a UTM Shimadzu AG 100 with a crosshead speed of 1.2 mm / min.
[0052] 3. Impact strength: The results of the Izod impact test are expressed by the kinetic energy consumed by the pendulum to break the sample. The test specimens used in the test are notched specimens. The Izod impact strength is measured on the CEAST Izod tester.
[0053] 4. Glass transition temperature: The glass transition temperature measures the thermal stability of the material. The test was conducted on a differential scanning calorimeter (model DSC3500Sirius) from NETZSCH, Germany. The sample was heated from -20°C to 230°C in a nitrogen atmosphere, kept constant for 5 minutes to eliminate the thermal history, then cooled by -20°C, and heated to 200°C again. The gas flow rate was 50 mL / min, and the heating and cooling rates were both 10°C / min.
[0054] The performance test results of Example 1 and the comparative example are shown in the following table:
[0055]
[0056] See Table 1 for the performance test results of Example 1 and the comparative example. It can be seen from the table that the present invention combines β-naphthol trifunctional resin with diethylenetriamine to make its product β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material have better mechanical properties and thermal stability than industrial epoxy resin, can meet engineering requirements, and can achieve the purpose of the present invention.
[0057] Example 2
[0058] A method for preparing a β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material comprises the following steps:
[0059] A 2L three-necked flask equipped with a mechanical stirrer and a condenser is placed in a constant temperature heating device. In the presence of an alkaline medium, 1.2 mol of β-naphthol and 2.3 mol of formaldehyde are added to the flask. Stir at a temperature of 60°C for 2 hours, then add 3.4 mol of epichlorohydrin to the reaction flask, and drip into an aqueous solution of NaOH (2.5 mol, 40% concentration solution). After the addition is completed, the temperature is raised to 80°C, the reaction mixture is stirred for 3.5 hours, and then 55 mL of methyl ethyl ketone is added as a solvent to maintain the viscosity of the resin. Desalination is performed by vacuum distillation, and then the resin is distilled at 118°C for 4 hours to remove excess water, methyl ethyl ketone and epichlorohydrin, and cooled at room temperature to obtain a dark yellow, odorless β-naphthol trifunctional resin with a yield of 83%.
[0060] The invention discloses a preparation method of a β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material, comprising the following steps: reacting the β-naphthol trifunctional resin: diethylenetriamine: carbon fiber at a molar ratio of 85:10:30. Diethylenetriamine is used as a curing agent, the β-naphthol trifunctional resin and diethylenetriamine are mixed evenly according to the required amount, and coated on 16 15cm carbon fiber cloths by hand lay-up process. Stacked between two polytetrafluoroethylene sheets. All sheets are kept at 80°C between two plates of a molding press for 90 minutes of high temperature curing, and finally pressed at 82°C for 4 minutes under a pressure of 50psi to flatten them. The prepared β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material is cooled at room temperature, taken out from the two plates of the molding press, and all dimensions of the composite sheet are measured after the polytetrafluoroethylene sheet is removed. The β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material (NCD) has a tensile strength of 81.2 MPa, a flexural strength of 195.8 MPa, an impact strength of 7.91 J / cm, and a glass transition temperature of 183°C.
[0061] Example 3
[0062] A method for preparing a β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material comprises the following steps:
[0063] A 2L three-necked flask equipped with a mechanical stirrer and a condenser is placed in a constant temperature heating device. In the presence of an alkaline medium, 1.0 mol of β-naphthol and 2.0 mol of formaldehyde are added to the flask. Stir at a temperature of 55°C for 1.5 hours, then add 3 mol of epichlorohydrin to the reaction flask, and drop into an aqueous solution of NaOH (2.2 mol, 40% concentration solution). After the addition is completed, the temperature is raised to 80°C, the reaction mixture is stirred for 3 hours, and then 50 mL of methyl ethyl ketone is added as a solvent to maintain the viscosity of the resin. Desalination is performed by vacuum distillation, and then the resin is distilled at 118°C for 3h to remove excess water, methyl ethyl ketone and epichlorohydrin, and cooled at room temperature to obtain a dark yellow, odorless β-naphthol trifunctional resin with a yield of 87%.
[0064] The invention discloses a preparation method of a β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material, comprising the following steps: reacting the β-naphthol trifunctional resin: diethylenetriamine: carbon fiber at a molar ratio of 70:1:10. Diethylenetriamine is used as a curing agent, the β-naphthol trifunctional resin and diethylenetriamine are mixed evenly according to the required amount, and coated on 12 15cm carbon fiber cloths by hand lay-up process. Stacked between two polytetrafluoroethylene sheets. All sheets are kept at a high temperature of 80°C between two plates of a molding press for 90 minutes for curing, and finally pressed at 83°C for 2 minutes under a pressure of 50psi to flatten them. The prepared β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material is cooled at room temperature, taken out from the two plates of the molding press, and all dimensions of the composite sheet are measured after the polytetrafluoroethylene sheet is removed. The β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material (NCD) has a tensile strength of 80.0 MPa, a flexural strength of 190.5 MPa, an impact strength of 7.8 J / cm, and a glass transition temperature of 181°C.
[0065] Example 4
[0066] A method for preparing a β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material comprises the following steps:
[0067] A 2L three-necked flask equipped with a mechanical stirrer and a condenser is placed in a constant temperature heating device. In the presence of an alkaline medium, 1.0 mol of β-naphthol and 1.5 mol of formaldehyde are added to the flask. Stir at a temperature of 45°C for 1.5 hours, then add 2 mol of epichlorohydrin to the reaction flask, and drop into an aqueous solution of NaOH (2.2 mol, 40% concentration solution). After the addition is completed, the temperature is raised to 70°C, the reaction mixture is stirred for 3 hours, and then 50 mL of methyl ethyl ketone is added as a solvent to maintain the viscosity of the resin. Desalination is performed by vacuum distillation, and then the resin is distilled at 118°C for 3h to remove excess water, methyl ethyl ketone and epichlorohydrin, and cooled at room temperature to obtain a dark yellow, odorless β-naphthol trifunctional resin with a yield of 80%.
[0068] The invention discloses a preparation method of a β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material, comprising the following steps: reacting the β-naphthol trifunctional resin: diethylenetriamine: carbon fiber at a molar ratio of 75:5:25. Diethylenetriamine is used as a curing agent, the β-naphthol trifunctional resin and diethylenetriamine are mixed evenly according to the required amount, and coated on 16 12cm carbon fiber cloths by hand lay-up process. Stacked between two polytetrafluoroethylene sheets. All sheets are kept at a high temperature of 70°C between two plates of a molding press for 2 hours for curing, and finally pressed at 84°C for 4 minutes under a pressure of 45psi to flatten them. The prepared β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material is cooled at room temperature, taken out from the two plates of the molding press, and all dimensions of the composite sheet are measured after the polytetrafluoroethylene sheet is removed. The β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material (NCD) has a tensile strength of 80.6 MPa, a flexural strength of 194.2 MPa, an impact strength of 7.89 J / cm, and a glass transition temperature of 180°C.
[0069] Example 5
[0070] A method for preparing a β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material comprises the following steps:
[0071] A 2L three-necked flask equipped with a mechanical stirrer and a condenser is placed in a constant temperature heating device. In the presence of an alkaline medium, 0.8 mol of β-naphthol and 2.5 mol of formaldehyde are added to the flask. Stir at a temperature of 65°C for 2.5 hours, then add 4 mol of epichlorohydrin to the reaction flask, and drop into an aqueous solution of NaOH (2 mol, 40% concentration solution). After the addition is completed, the temperature is raised to 90°C, the reaction mixture is stirred for 4 hours, and then 100 mL of methyl ethyl ketone is added as a solvent to maintain the viscosity of the resin. Desalination is performed by vacuum distillation, and then the resin is distilled at 118°C for 3.5 hours to remove excess water, methyl ethyl ketone and epichlorohydrin, and cooled at room temperature to obtain a dark yellow, odorless β-naphthol trifunctional resin with a yield of 85%.
[0072] The invention discloses a preparation method of a β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material, comprising the following steps: reacting the β-naphthol trifunctional resin: diethylenetriamine: carbon fiber at a molar ratio of 75:10:25. Diethylenetriamine is used as a curing agent, the β-naphthol trifunctional resin and diethylenetriamine are mixed evenly according to the required amount, and coated on 16 12cm carbon fiber cloths by hand lay-up process. Stacked between two polytetrafluoroethylene sheets. All sheets are kept at a high temperature of 100°C between two plates of a molding press for 2.5 hours of curing, and finally pressed at 85°C for 5 minutes under a pressure of 60psi to flatten them. The prepared β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material is cooled at room temperature, taken out from the two plates of the molding press, and all dimensions of the composite sheet are measured after the polytetrafluoroethylene sheet is removed. The β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material (NCD) has a tensile strength of 82.3 MPa, a flexural strength of 198.9 MPa, an impact strength of 7.97 J / cm, and a glass transition temperature of 182°C.
[0073] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material, characterized in that: include: The β-naphthol trifunctional resin and diethylenetriamine are uniformly mixed and coated on a plurality of carbon fibers, and after high temperature curing, pressing and cooling, a β-naphthol trifunctional resin / carbon fiber / diethylenetriamine composite material is obtained; The beta-naphthol-based trifunctional resin is prepared by polymerization of beta-naphthol, formaldehyde and epichlorohydrin under alkaline medium conditions.
2. The method for preparing the β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material according to claim 1, characterized in that: The molar ratio of the beta-naphthol trifunctional resin: diethylenetriamine: carbon fiber is (70-85): (1-10): (10-30).
3. The method for preparing the β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material according to claim 1, characterized in that: The high temperature curing temperature is 70-100° C.; the high temperature curing time is 1.5-2.5 hours; the pressing pressure is 45-60 psi; the pressing temperature is 80-85° C.; and the pressing time is 2-5 minutes.
4. The method for preparing the β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material according to claim 1, characterized in that: The preparation method of the β-naphthol-based trifunctional resin comprises: adding β-naphthol and formaldehyde into a beaker, heating and stirring them uniformly, adding epichlorohydrin and a NaOH aqueous solution, heating and stirring them uniformly, adding methyl ethyl ketone, desalting, and distilling the resin to obtain the β-naphthol-based trifunctional resin.
5. The method for preparing the β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material according to claim 4, characterized in that: The dosage ratio of the β-naphthol: formaldehyde: epichlorohydrin: NaOH aqueous solution: methyl ethyl ketone is (0.8-1.2) mol: (1.5-2.5) mol: (2-4) mol: (2-2.5) mol: (50-100) mL; the mass fraction of the NaOH aqueous solution is 40%.
6. The method for preparing the β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material according to claim 4, characterized in that: The heating and stirring is performed at a temperature of 45-65° C. and for a time of 1.5-2.5 h.
7. The method for preparing the β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material according to claim 4, characterized in that: The temperature of the heating and stirring is 70-90°C and the time is 3-4h.
8. The method for preparing the β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material according to claim 4, characterized in that: The temperature of the distilled resin is 118° C., and the time of the distilled resin is 3-4 hours. The reaction yield of the β-naphthol trifunctional resin is 80%-87%.
9. The β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The tensile strength is 80.0-82.4MPa, the flexural strength is 190.5-199.2MPa, the impact strength is 7.80-8.00J / cm, and the glass transition temperature is 180-183℃.
10. Use of the β-naphthol-based trifunctional resin / carbon fiber / diethylenetriamine composite material prepared by the preparation method according to any one of claims 1 to 8 in the preparation of insulating materials.
Citation Information
Cited By
Multi-chemical-medium-resistant cross-linked network coating and preparation method thereof
CN121450189A